A symbolic representation of Wellington: how participatory painting processes enabled a more inclusive urban narrative. Issue 4 (2nd October 2018) - Kale, Amber
Abstract : In this article I examine how a participatory painting project in Wellington enhanced cross-cultural understanding between former refugee and host-society participants and enabled a more inclusive urban narrative. In light of the current global humanitarian crisis, a climate of fear has arisen around refugees, which is often exacerbated by the media perpetuating misinformation and negative stereotypes. To counteract misrepresentation, the painting project provided a space for participants to share their lived experiences of home, belonging, and public visibility. A scholar activist orientation was employed, informed by a participatory action research epistemology. These philosophical foundations influenced a qualitative multi-method methodology consisting of painting workshops, semi-structured interviews, participant observation, and public feedback. Through the process of painting a collaborative mural, participants used symbolism to deconstruct language barriers, elicit new ideas, and co-construct a more inclusive narrative whereby differences were negotiated rather than excluded, oppressed, or assimilated. In this manner, social unity was achieved in such a way that it that did not over-ride diversity.